(untitled) (CIPEEX, 2025)
The aim of this systematic review was to evaluate the best therapeutic protocol for the treatment of root canal obliteration (RCO) following traumatic dental injury. The article search was conducted through PubMed, Lilacs, Scopus, and Cochrane Library portals. The selected articles were identified from the titles and abstracts, considering the following inclusion criteria: 1- In vivo studies, 2- Studies in humans. The database search found 2066 articles, and after applying the selection criteria, a total of 19 articles were included: 8 literature reviews, 6 clinical case reports, 2 literature reviews + case reports, 1 longitudinal study, 1 retrospective study, and 1 systematic review. From the obtained results, two initial therapies were described for this condition: early endodontic treatment as a preventive measure against root canal obliteration, and patient follow-up. If signs and symptoms suggesting pulp necrosis and periradicular lesion development occurred, endodontic therapy would be indicated. In summary, the selected articles suggest that pulp necrosis and periradicular lesions are not common complications of root canal obliteration. If there is a preference for preventive endodontic treatment, it would only be as a routine procedure, with most indications being unnecessary, as the majority of teeth with RCO do not necessarily develop pulp necrosis and periradicular lesions.